Policy Trends and Tensions in Accountability for Educational Management and Services in Canada - Jaafar, Sonia Ben; Anderson, Stephen (Alberta Journal of Educational Research, 2007)
Accountability structures and processes have become such an integral part of education policy development and implementation that Ranson (2003) argues, “accountability is no longer merely an important instrument or component within the system, but constitutes the system itself” (p. 459). This argument is supported by the growth of an orientation in public education reforms toward the premise that more accountable schools are better schools. Canada fits the global trend that levers educational reforms through accountability measures.